SAS programming for elementary statistics : getting started - Goad, Carla L. (Boca Raton : Chapman & Hall/CRC, 2020)
SAS for Elementary Statistics: Getting Started provides an introduction to SAS programming for those who have experience with introductory statistical methods. It is also an excellent programming supplement for an introductory statistics course. It is appropriate for the beginning programmer with no prior SAS experience and the researcher who would like to refresh SAS programming skills. These lessons are those the author has found successful in the classroom. Strengths of this book include the following: Examples are easy to follow and understand. Chapters have user-friendly text and objectives. Each chapter has clear objectives with SAS syntax and output results given. Objectives are stated as tasks with detailed step-by-step instructions. Programming notes based on the author's experience occur throughout the book. The author assists the reader in making sense of the error messages in the SAS log. Brief reviews of statistical methods are included in chapters accompanying the corresponding SAS procedures. Easy transition from user terminology to SAS terminology is provided. The ability to select or suppress results using Output Delivery System (ODS) is made simple. Reading and writing to external files are among the most used SAS skills, and these concepts are clearly presented. The IMPORT and EXPORT procedures and ODS are used to accomplish these tasks. Statistical Graphics procedures and SAS/GRAPH can be quite challenging to learn, but these are presented in a very achievable format. Basic graph construction is first introduced then readers learn how to add color, pattern, and other enhancements to graphics images.
1. Introduction to SAS Programming Environment 2. DATA Step Information 1 3. Summarizing Data Basics 4. DATA Step Information -- 2 5. Beginning Charts 6. One and Two Population Hypothesis Tests about the Means 7. One-way ANOVA Methods, Non-Parametric Methods and Ranking Data 8. Data Step Information 3 -- Reading Data Files & Labeling Variables 9. Frequency Analysis 10. Summarizing a Data Table in a Formal Report 11. Regression and Correlation Analysis 12. SAS Libraries and Permanent SAS Data Sets 13. DATA Step Information 4 -- SAS Probability Functions 14. Reading and Writing Data Files 15. DATA Step Information 5 -- DO Loops, Arrays, and Random Number Generation 16. Statistical Graphics Procedures 17. SAS/GRAPH Procedures 18. Formatting Responses 19. Output Delivery System (ODS) 20. Miscellaneous Topics
OCLC-licensed vendor bibliographic record.
Keywords: Mathematical statistics -- Data processing; SAS (Computer program language); MATHEMATICS / Probability & Statistics / General; REFERENCE / General